Seroepidemiology of Canine parvovirus infection in dogs - Sendow, Indrawati; Syafriati, Tatty (Indonesian Journal of Animal and Veterinary Sciences, 2004)
Canine parvovirus is an acute and fatal viral disease in dogs. A total of 209 local, cross breed and breed dogs sera from Kodya Bogor, Kabupaten Bogor, Sukabumi, and Jakarta, had been tested using Haemagglutination Inhibition Test (HI) with pig red blood cells. A total of 64 breed and cross breed dogs from Sukabumi and Kodya Bogor, were used as a sentinel dogs to study the epidemiology of Canine parvovirus (CPV) infection and its immunological responses caused by vaccination. The results indicated that 78% (95) breed and cross bred dogs and 59% (51) local dogs had antibody to CPV. Sentinel dogs results indicated that dogs had been vaccinated showed antibody response with the varied titre dependant upon prevaccination titre. Low prevaccinated titre gave better response than protective level titre. From 19 puppies observed, Maternal antibodi were still detected until 5 weeks old puppies. First vaccination given at less than 3 months old, should be boosted after 3 months old puppied. Antibodi titre produced by natural infection will keep untill 2 years. These data concluded that the dog condition and time of vaccination will affect the optimum antibody response. Â  Key words: Canine parvovirus, haemagglutination inhibition, isolation